Veno‐venous extracorporeal membrane oxygenation for severe pneumonia: COVID‐19 case in Japan. Issue 1 (14th April 2020) - Taniguchi, Hayato; Ogawa, Fumihiro; Honzawa, Hiroshi; Yamaguchi, Keishi; Niida, Shoko; Shinohara, Mafumi; Takahashi, Kohei; Iwashita, Masayuki; Abe, Takeru; Kubo, Sousuke; Kudo, Makoto; Takeuchi, Ichiro
Abstract : Background: Veno‐venous extracorporeal membrane oxygenation (VV‐ECMO) is one of the ultimate treatments for acute respiratory failure. However, the effectiveness of ECMO in patients with novel coronavirus disease (COVID‐19) is unknown. Case Presentation: A 72‐year‐old woman who was a passenger of a cruise ship tested positive for the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) while in quarantine on board using throat swab. Three days after admission, her condition deteriorated, and she was subsequently intubated. On day 6, VV‐ECMO was introduced. Lopinavir/ritonavir was given; continuous renal replacement therapy was also introduced. On day 10, her chest radiography and lung compliance improved. She was weaned off ECMO on day 12. Conclusion: Treatment of severe pneumonia in COVID‐19 by ECMO should recognize lung plasticity considering time to ECMO introduction and interstitial biomarkers. In Japan, centralization of ECMO patients has not been sufficient. Thus, we suggest nationwide centralization and further research to respond to the crisis caused by COVID‐19. Abstract : ECMO is one of the treatment options in severe ARDS by SARS‐CoV‐2. It is important to recognize lung plasticity. Centralization of COVID‐19 ECMO patients may be effective in Japan.